Strategic Marketing and Competitive Advantage: A Systematic Literature Review in Dynamic Markets - Mutiara Gilang Purnama Sakti; Vandwuis Yang; Sri Rahayu Widiningsih; Herlinawati (eCo-Buss, 2025)
This study investigates the role of strategic marketing in fostering sustainable competitive advantage through a systematic literature review of 25 peer-reviewed articles published between 2021 and 2025. Using thematic synthesis, the review identifies eight core themes: strategic agility and adaptability, customer-centric innovation, digital transformation, resource-based strategy and leadership, market orientation and foresight, integrated marketing strategy, brand co-creation and positioning, and sustainable and cultural marketing. These themes illustrate how strategic marketing integrates internal capabilities, digital infrastructure, and stakeholder engagement to enhance organizational responsiveness, innovation, and differentiation in dynamic environments. The findings reinforce theoretical perspectives such as the Resource-Based View (RBV) and Dynamic Capabilities Theory, while also offering practical insights for aligning marketing strategies with digital adaptation, customer value, and long-term strategic leadership. The study highlights methodological gaps particularly the limited use of longitudinal and cross-regional analyses and recommends future research adopt mixed methods and multilevel designs to better capture the evolving relationship between strategic marketing and competitive advantage across diverse organizational and institutional contexts.